Screening Children with a History of Maltreatment for PTSD in Frontline Social Care Organisations: An Explorative Study. (22nd December 2021) - Duffy, Michael; Walsh, Colm; Mulholland, Ciaran; Davidson, Gavin; Best, Paul; Bunting, Lisa; Herron, Stephen; Quinn, Paul; Gillanders, Catherine; Sheehan, Caroline; Devaney, John
Abstract : Traumatic experiences during childhood are common and often lead to chronic mental health conditions such as posttraumatic stress disorder (PTSD). The primary aim of this study was to determine whether a well‐validated screening tool for PTSD administered in frontline services effectively identifies diagnosable PTSD in young people with a history of maltreatment. In total, 141 young people in community care settings were screened using three screening instruments (Child Revised Impact of Events Scale‐8; Generalised Anxiety Disorder‐2; Patient Health Questionnaire‐2). Participants described a range of adverse life events: 110 of the 141 participants reported at least one adverse life experience (mean number for the total sample was 2.8), with 44.2 per cent ( n = 46) experiencing at least one form of interpersonal trauma; and 102 participants (72.3 per cent) screened positively for probable PTSD and subsequent mental health assessments confirmed this condition in 64.7 per cent of these participants. Further, 36.9 per cent ( n = 52) and 46.8 per cent ( n = 66) met the threshold for probable depression and anxiety, respectively. Three items were associated with positive PTSD screens: a history of being on the child protection register, previous mental health contact and interpersonal index trauma. Interpersonal traumas were also associated with higher risks of offending. It seems feasible to use screening measures effectively within frontline social care services if staff are provided with appropriate training and support to identify young people with PTSD who may benefit from evidence‐based mental health therapies. Key Practitioner Messages: There is strong evidence of the link between childhood adversities and poor mental health, including PTSD. This study found that a short instrument can be embedded within social care services to screen children and young people for PTSD. It is important that frontline staff have the necessary training and tools to understand the effects of trauma and screen children's mental health in order to facilitate access to effective therapies at an early stage.